PENGARUH BERBAGAI JENIS HERBISIDA TERHADAP PENGENDALIAN GULMA DAN HASIL TANAMAN PADI (Oriza sativa L.) DENGAN SISTEM TANAM BENIH LANGSUNG - Nalfin, Nalfin; made, Usman; latarang, Burhanuddin (AGROTEKBIS, 2018)
This study aims to know the effect of different types of herbicides on weed control and yield of rice ( Oryza sativa L . ) with direct seeding system. The research was conducted in Tolai village, Torue Sub-Districts, Parigi Moutong District, in August to November 2014. This study used a Randomized Block Design, consisting of five treatments, that are: Sihalofop-Butil Herbicides of 3 ml/plot, Penokxulam+Bentazone 1,2+3,75 ml/plot, fenoksapropâP-Etil of 1,56 ml/plot and Metil Metsulfuron of Â 1,2Â ml/plot, and without treatment ( control ). The result showed that the application of various types of herbicide at a dose of 3 ml/ plot up to 1,56 ml / plot on observations time of 3 , 7 and 14 DAA causes mild symptoms only in rice plants . These herbicides can be used to increase rice production with an effective dose of herbicide application is Penokxulam+Bentazone 1,2+3,75 ml/plot, and fenoksapropâP-Etil 1,56 ml/plot.Â Key words : Direct sowing planting, Herbicide, Rice, Weed.